Mechanism of superconductivity and electron-hole doping asymmetry in κ-type molecular conductors - Hiroshi Watanabe (Nature Portfolio, 2019)
The mechanism of unconventional superconductivity in molecular conductors remains controversial. Here, Watanabe et al. theoretically study and report electron-hole doping asymmetry and competing orders with superconductivity in a doped molecular Mott system.